Transcriptomic analysis reveals yolk accumulation mechanism from the hepatopancreas to ovary in the pacific white shrimp Litopenaeus vannamei - Li, Zhi; Zhou, Minyu; Ruan, Yao; Chen, Xiaoli; Ren, Chunhua; Yang, Hao; Zhang, Xin; Liu, Jinshang; Li, Huo; Zhang, Lvping; Hu, Chaoqun; Chen, Ting; et al. (Frontiers in Marine Science, 2022)
The Pacific white shrimp Litopenaeus vannamei is an economically important penaeid species worldwide. Under farming conditions, the full ovarian maturation of L. vannamei generally depends on the combination of artificial ablation of unilateral eyestalk and feeding high-quality natural diets, suggesting that nutrient accumulation is important to ovarian maturation. In this study, we aimed to investigate the gene expression related to nutritional accumulation in L. vannamei during ovarian development by transcriptomic analysis. A total of 52.45 Gb of high-quality transcriptome data were obtained from 8 samples from the hepatopancreas and ovaries from shrimp in gonadal developmental stages I-IV. A total of 23,149 expressed genes were detected, of which 19,852 were known genes and 3,297 were novel genes. Our study found that genes related to amino acid, carbohydrate and lipid metabolism were expressed at higher levels in the hepatopancreas than in the ovary. The genes for most lipoproteins and their receptors were predominantly expressed in the hepatopancreas, while vitellogenin receptor (VgR) was specifically expressed in the ovary. Moreover, two vitellogenin (Vg) genes were identified, in which one was specifically expressed in the hepatopancreas and defined as Hp-Vg, and the other was specifically expressed in the ovary and defined as Ov-Vg. In addition, genes related to carotenoid metabolism were enriched in the hepatopancreas. This study provides solid evidence that the hepatopancreas is the major exogenous vitellogenesis site for ovarian maturation of L. vannamei. Two distinct Vg genes perform exogenous and endogenous vitellogenesis in the hepatopancreas and ovary in L. vannamei, respectively. The results of this study also presented some new insights for understanding the nutritional dynamics from the hepatopancreas to ovary during ovarian maturation in penaeids.